The Effect of E-Service Quality and E-Wom on Purchase Decisions Through the Tiktok Shop Application among College Students in Surabaya - Cholishah Anas Irhamna; Rizky Dermawan (Jurnal Ekonomi dan Bisnis Digital, 2023)
The purpose of this script is to explore how E-Service Quality and Electronic Word of Mouth (E-WOM) influence purchasing decisions through the TikTok Shop app. TikTok Shop experienced a decline of 12.4% in the first quarter of 2022, demonstrating that this does not guarantee that TikTok Shop will always be at the top. Kotler & Armstrong (2016:177) found that buying decisions focus on how individuals and groups choose, acquire, and use experiences, services, ideas, and products to meet desires and needs that are part of consumer behavior. Quantitative analysis is the method used in this study. Non-probability sampling and Purposive Sampling techniques are used for sample collection. The survey used a Likert scale questionnaire with a sample of 100 respondents and the population of students in the city of Surabaya. Partial Least squares (PLS) are used to check research findings. It has been found that E-Service Quality and E-WOM have been shown to influence purchasing decisions through TikTok Shop positively.